Optimising CO2 level and light quality for enhanced whole-cell biotransformation reactions in Synechocystis sp. PCC 6803 - Hubáček, Michal; Nikkanen, Lauri; Allahverdiyeva, Yagut (BioMed Central, 2026)
Cyanobacteria are emerging as a promising platform for whole-cell biotransformation, harnessing solar energy to drive biocatalytic reactions through recombinant enzymes. However, optimisation remains challenging due to the complexity of the cyanobacterial metabolism and the regulatory framework in which heterologous enzymes operate. While many enzymes have been deployed for light-driven whole-cell biotransformations, the different experimental conditions used between studies make direct comparison and systematic improvement difficult. We investigated the performance of two Baeyer-Villiger monooxygenases (BVMO) and the ene-reductase YqjM, heterologously expressed in the model cyanobacterium Synechocystis sp. PCC 6803, under varying growth and production conditions. NADPH and O2 availability, along with protein accumulation levels, were examined as potential bottlenecks affecting enzyme activity. A 4-fold improvement in specific activity of BVMOs was achieved when cultures were grown under elevated CO2, and a 2-fold improvement was observed under broad white light enriched with red and blue wavelengths. Elevated CO2 cultivations enhanced BVMO protein accumulation, while YqjM levels and activity remained unchanged. In contrast, the modified light spectrum led to a non-significant increase in BVMO accumulation but significantly enhanced specific activity under ambient CO2 conditions. These findings demonstrate the importance of a tailored optimisation strategy for each enzyme in cyanobacterial light-driven whole-cell biotransformation and shed light on the complex physiological responses of production strains to environmental conditions.